2017
DOI: 10.1002/hed.25002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of general anesthesia and intubation on parathyroid levels in normal patients and those with hyperparathyroidism

Abstract: General anesthesia and endotracheal intubation causes an immediate, steep, and significant PTH elevation in patients with primary HPT but only a minor change in healthy adults. The difference may be attributed to an impaired adrenergic response in patients with primary HPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…A reduction in intraoperative PTH by more than 50% after the procedure is a predictive factor [22,23] and may be prevented by preoperative supplementation with bisphosphonates [24,25]. Age is not a relevant contributing factor for the occurrence of complications [26,27], while anesthesia can often cause sudden elevation of PTH levels in patients suffering from hyperparathyroidism [28,29] and can worsen renal functions [30,31]. The latest works shows that minimally invasive radio-guided parathyroidectomy using a very low dose of Tc-99 MIBI, even without an intraoperative assay or a frozen section analysis, resulted in an excellent cure rate [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in intraoperative PTH by more than 50% after the procedure is a predictive factor [22,23] and may be prevented by preoperative supplementation with bisphosphonates [24,25]. Age is not a relevant contributing factor for the occurrence of complications [26,27], while anesthesia can often cause sudden elevation of PTH levels in patients suffering from hyperparathyroidism [28,29] and can worsen renal functions [30,31]. The latest works shows that minimally invasive radio-guided parathyroidectomy using a very low dose of Tc-99 MIBI, even without an intraoperative assay or a frozen section analysis, resulted in an excellent cure rate [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…But on the other hand, PTH level influenced by some many factors including stress, stress hormones (such as catecholamines, cortisol and inulin), general anesthesia and endotracheal intubation (the most stress-baring procedure), calcium, magnesium, vitamin D, anesthetic agents (propofol) and laparoscopic surgeries (elevated blood CO 2 may change blood pH and cause a shift of ionized calcium [15,16]. Also previous studies reported that propofol influence PTH level; Kivela et al results suggests that there is no need to avoid propofol during parathyroid surgery as previously suggested [16]. Whether propofol affects PTH level or not is still debate so we prefer inhalation anesthesia and desflurane as inhalation anaesthetic.…”
Section: Discussionmentioning
confidence: 99%